Institutional trading around the ex-dividend day. (May 2016) - Ainsworth, Andrew; Fong, Kingsley YL; Gallagher, David R; Partington, Graham
This study uses the trading records of institutional equity funds to examine their ex-dividend trading behaviour. We argue that trading is influenced by the tax incentives facing the fund, the characteristics of individual stocks and by changes in tax legislation. In aggregate, institutions trade to avoid the dividend and franking credit. Changes in tax incentives and the fund's tax status also affect ex-dividend day trading, with unit trusts dominating the dividend avoidance trades. The results indicate that taxes, transactions costs and the cum-dividend price run-up influence the trading of institutional investors around the ex-dividend day.